Analisis Prototype Smart Door Lock Berbasis RFID, Keypad dan Sensor Gerak - Fathiah; Mursyidin; Baihaqi; Muhammad Rizal Fachri (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
In today's world, technological innovations make it easier to choose doors that enhance security, such as those with digital locks that integrate biometric systems such as fingerprint scanners or facial recognition. Previous research has successfully developed a prototype smart door locking system that combines RFID technology, keypads and motion sensors. Radio Frequency Identification (RFID) technology and keypads are two key components of modern security systems. Their use can enhance security in applications ranging from door access control to storage solutions. Motion sensors are devices designed to detect movement in a given area. They work by monitoring changes in the physical environment, such as changes in temperature, sound waves or electromagnetic fields, caused by the movement of objects or people. The method used in this research is the End User Computing Satisfaction (EUCS) approach, together with the BlackBox method. EUCS is a technique used to measure user satisfaction with a system, emphasising the user's experience while interacting with the system. Based on the analysis of the evaluation results, it can be concluded that the RFID-based smart door lock system, equipped with a keypad and a sensor, meets the usability criteria and falls into the good or acceptable category for users. In addition, the black box test results show that the system is functioning as expected.